Preparation, Characterization and Antibacterial Property Analysis of Cellulose Nanocrystals (CNC) and Chitosan Nanoparticles Fine-Tuned Starch Film - Zilong Deng; Zixuan Wu; Xiao Tan; Fangkun Deng; Yaobang Chen; Yanping Chen; Hongcai Zhang (Molecules, 2022)
To improve the mechanical and antibacterial properties of traditional starch-based film, herein, cellulose nanocrystals (CNCs) and chitosan nanoparticles (CS NPs) were introduced to potato starch (PS, film-forming matrix) for the preparation of nanocomposite film without incorporation of additional antibacterial agents. CNCs with varied concentrations were added to PS and CS NPs composite system to evaluate the optimal film performance. The results showed that tensile strength (TS) of nanocomposite film with 0, 0.01, 0.05, and 0.1% (w/w) CNCs incorporation were 41, 46, 47 and 41 MPa, respectively. The elongation at break (EAB) reached 12.5, 10.2, 7.1 and 13.3%, respectively. Due to the reinforcing effect of CNCs, surface morphology and structural properties of nanocomposite film were altered. TGA analysis confirmed the existence of hydrogen bondings and electrostatic attractions between components in the film-forming matrix. The prepared nanocomposite films showed good antibacterial properties against both E. coli and S. aureus. The nanocomposite film, consist of three most abundant biodegradable polymers, could potentially serve as antibacterial packaging films with strong mechanical properties for food and allied industries.